Validation of the academic misconduct questionnaire: exploring predictors of student misconduct - Ana Cristina Veríssimo; Joselina Barbosa; Milton Severo; Paula Mena Matos; Pedro Oliveira; Laura Ribeiro (Medical Education Online)
Multiple instruments have been used to assess academic misconduct, yet robust psychometric evidence has been reported only for a few. This study aims to determine the validity and dimensionality of a novel Academic Misconduct Questionnaire (AMQ) and to explore differences between students who engage in distinct misbehaviours. A diverse sample of health and non-health students replied to the AMQ. Exploratory and confirmatory factor analyses were conducted using two subsamples. Predictive models were computed for the AMQ and its dimensions. The questionnaire showed good validity and reliability, revealing eight dimensions related to Cheating during (two forms) and prior Exams, Plagiarism, Fraud in Academic Work, Impersonation (assessment), Signature Forgery in attendance sheets and Not Reporting peer misconduct. The predictors of student engagement in each form of misconduct differed, except for perceiving greater peer fraud, which increased the propensity for all misbehaviours. Perceiving higher sanctions reduced the propensity to engage in most forms, while gender played a role in half of them. First-year students were more likely to Not Reporting peer misconduct and less likely to disclose Fraud in Academic Work and Signature Forgery than those in more advanced years. Health students scored higher in most misbehaviours, especially compared to Economics/Law, Social Sciences and Arts/Humanities, while the latter two disclosed higher Signature Forgery. This study proposes a valid instrument to assess academic misconduct in university students. The predictive models helped to better understand differences between students who engaged in distinct misbehaviours, enabling more targeted interventions.